Design, synthesis and biological evaluation of novel azaspiro analogs of linezolid as antibacterial and antitubercular agents - Gadekar, Pradip K.; Roychowdhury, Abhijit; Kharkar, Prashant S.; Khedkar, Vijay M.; Arkile, Manisha A.; Manek, Hardik; Sarkar, Dhiman; Sharma, Rajiv; Vijayakumar, V.; Sarveswari, S. (European Journal of Medicinal Chemistry, 2016)
The design, synthesis and antimicrobial evaluation of a novel series of azaspiro analogues of linezolid (1) have been described. Linezolid comprises of a morpholine ring which is known for its metabolism related liabilities. Therefore, the key modification made in the linezolid structure was the replacement of morpholine moiety with its bioisostere, 2-oxa-6-azaspiro[3.3]heptane. Furthermore, the replacement of N-acetyl terminal of 1 with various aromatic or aliphatic functionalities was carried out. The title compounds were evaluated against a panel of Gram-positive and Gram-negative bacteria and Mycobacterium tuberculosis. Subsequent structure-activity relationship (SAR) studies identified several compounds with mixed antibacterial and antitubercular profiles. Compound 22 (IC50 0.72, 0.51, 0.88, 0.49 mu g/mL for Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus, Bacillus subtilis, respectively) exhibited similar antibacterial profile as I. The N-acetyl derivative 18 was similar to 1 in antitubercular profile. Thus, the present study successfully demonstrated the use of azaspiro substructure in the medicinal chemistry of antibacterial and antitubercular agents. (C) 2016 Elsevier Masson SAS. All rights reserved.